Evaluation and ranking of insurance companies by combining TOPSIS and the interval fuzzy rough sets - Mimovic, Predrag; Tadic, Danijela; Borota-Tisma, Ankica; Nestic, Snezana; Gil Lafuente, Jaime (Serbian Journal of Management, 2021)
Corporate and organizational performance assessment is an important activity for both the managers and other stakeholders, as it provides them with an asset to evaluate their own strengths and weaknesses in relation to the competition, as well as guidelines for selecting appropriate measures to address the existing problems. The issue of criteria selection has been overcome through the literature review and the issue of criteria weights is handled by applying group decision making procedure. The procedure itself consists of using predefined linguistic expressions that are modelled by triangular fuzzy numbers and the aggregation of decision makers’ opinion based on the rules of rough sets algebra. The values of the decision matrix are determined by prognosis method and they are described by crisp values. The proposed algorithm is tested on the insurance companies that operate in the Republic of Serbia.
Keywords: group decision making; interval –valued fuzzy-rough numbers; TOPSIS; insurance